2020
DOI: 10.1002/ana.25893
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity–Specificity of Tau and Amyloid β Positron Emission Tomography in Frontotemporal Lobar Degeneration

Abstract: Objective: To examine associations between tau and amyloid β (Aβ) molecular positron emission tomography (PET) and both Alzheimer-related pathology and 4-repeat tau pathology in autopsy-confirmed frontotemporal lobar degeneration (FTLD). Methods: Twenty-four patients had [ 18 F]-flortaucipir-PET and died with FTLD (progressive supranuclear palsy [PSP], n = 10; corticobasal degeneration [CBD], n = 10; FTLD-TDP, n = 3; and Pick disease, n = 1). All but 1 had Pittsburgh compound B (PiB)-PET. Braak staging, Aβ pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 38 publications
(41 citation statements)
references
References 49 publications
1
38
2
Order By: Relevance
“…Off-target binding is well-characterised for 18 F-flortaucipir, but this problem alone would still leave open the utility to quantify tau pathology in areas without significant mono-amine oxidase levels or neuromelanin, such as cerebellum and medial frontal cerebral cortex (22). However, recent PET-to-autopsy correlational studies suggested that 18 F-flortaucipir PET does not reliably correspond to post-mortem tau pathology in non-Alzheimer's tauopathies (13,23). This suggests that 18 F-flortaucipir lacks sensitivity in non-Alzheimer tau pathology.…”
Section: Discussionmentioning
confidence: 99%
“…Off-target binding is well-characterised for 18 F-flortaucipir, but this problem alone would still leave open the utility to quantify tau pathology in areas without significant mono-amine oxidase levels or neuromelanin, such as cerebellum and medial frontal cerebral cortex (22). However, recent PET-to-autopsy correlational studies suggested that 18 F-flortaucipir PET does not reliably correspond to post-mortem tau pathology in non-Alzheimer's tauopathies (13,23). This suggests that 18 F-flortaucipir lacks sensitivity in non-Alzheimer tau pathology.…”
Section: Discussionmentioning
confidence: 99%
“…Neuropathological evaluations were performed in accordance with current diagnostic protocol, as previously described. 19,20 Pathological diagnoses were rendered according to established criteria: PSP was diagnosed based on the presence of characteristic neuronal (pretangles and tangles) and glial lesions (tufted astrocytes and oligodendroglial coiled bodies) in vulnerable cortical and subcortical regions, 21 and CBD by the presence of cortical and subcortical neuronal and glial lesions (astrocytic plaques) and thread-like processes in gray and white matter 22 ; FTLD-TDP type A had TDP-43-immunoreactive neuronal cytoplasmic inclusions, dystrophic neurites, and intranuclear inclusions, while type B had predominantly neuronal cytoplasmic inclusions. 23 PiD showed argyrophilic and tau-immunoreactive Pick bodies, which were negative on Gallyas silver stain.…”
Section: Methodsmentioning
confidence: 99%
“…For example, current tau PET tracers cannot accurately distinguish between Braak stage 0 (absence of tauopathy) and Braak stage 1 (early tauopathy in the entorhinal cortex in the medial temporal lobe). 152,153,155,156 Until very recently, researchers also have been unable to pinpoint the precise area in the brain where tau accumulation in AD first begins using tau PET imaging. However, Sanchez et al recently reported findings that suggest that cortical tau pathology may begin in a region of the brain they call the "rhinal cortex"-a region defined anatomically using brain surface anatomy that is sampled during PET imaging.…”
Section: Imaging Ad Pathologymentioning
confidence: 99%
“…The development of tau-specific PET ligands has made it possible to investigate the measurement of tau deposition not only in AD but also in a wide range of non-AD tauopathies, including PSP, 155,[159][160][161][162] CBD, 155,[163][164][165][166] and Pick's disease. 155 However, FTP and other currently available tau tracers, when used to image non-AD pathology, have generally demonstrated low-affinity binding, significant off-target binding, and other characteristics that have resulted in limited sensitivity and specificity. 165,[167][168][169] These in vivo results converge with autoradiography studies that have shown absent-to-low binding of FTP to non-AD tauopathies.…”
Section: Imaging Non-ad Tau Pathologymentioning
confidence: 99%
See 1 more Smart Citation